Experimental study of a woven fiberglass composite delamination under impact shock - Olodo, E. T.; ADANHOUNME, VILLÉVO; Adjovi, E.C.; Shambina, Svetlana (My University, 2014)
This work is devoted to the experimental study of a glass/polyester composite laminate under impact shock. Based on a thermodynamic approach, the objective is the evaluation of specific interlaminar delamination energy in a multi-layer composite material under impact loading causing damage to it by cracking. For modeling impact loading, it is used an experimental device based on the principle of Charpy test which is to measure residual energy of a mass movement following a shock at speeds generally between 1 and 4 m/s, on a test piece cut of standardized dimensions requested in bending. Some of available energy is consumed by the rupture of the test piece. The results of this work showed that for impact test, mode I fracture energy is function of impact speed and the load fall energy. These results could be useful in the design of multilayer structures in composite materials subjected to impact loads.
Keywords: Interlaminar delamination; Specific delamination energy; Charpy test